134k views
0 votes
Solve the inequality.

Solve the inequality.-example-1
User FelixSFD
by
4.9k points

2 Answers

2 votes

Answer:

Let's solve your inequality step-by-step.


(x)/(3)-((x-1)/(2))\geq1

Step 1: Simplify both sides of the inequality.


(-1)/(6)x+(1)/(2)\geq1

Step 2: Subtract 1/2 from both sides.


(-1)/(6)x+(1)/(2)-(1)/(2)\geq1-(1)/(2)


(-1)/(6)x\geq(1)/(2)

Step 3: Multiply both sides by 6/(-1).


((6)/(-1))*((-1)/(6)x)\geq((6)/(-1))*((1)/(2))


x\leq-3

Answer:


x\leq-3 This is the answer

I hope this help you :)

User ManmeetP
by
4.8k points
6 votes

Answer:


x \leqslant - 3

option C is the right option.

Solution,


(x)/(3) - (x - 1)/(2) \geqslant 1 \\ = (2x - 3( x - 1))/(6) \geqslant 1 \\ = (2x - 3x + 3)/(6) * 6 \geqslant 6 \\ = 2x - 3x + 3 \geqslant 6 \\ = - x + 3 \geqslant 6 \\ = - x + 3 - 3 \geqslant 6 - 3 \\ = - x \geqslant 3 \\ = - ( - x) \leqslant - 3 \\ = x \leqslant - 3

hope this helps...

Good luck on your assignment

User RishiG
by
4.9k points